Adsorption of toxic dye using red seaweeds from synthetic aqueous solution and its application to industrial wastewater effluents - Al-Saeedi, Sameerah I.; Ashour, Mohamed; Alprol, Ahmed E. (Frontiers in Marine Science, 2023)
This study investigated the potential application of dried powder from red seaweed Pterocladia capillacea as an eco-friendly adsorbent for removing Crystal Violet Dye (CV dye) from a synthetic solution. The adsorption conditions for the adsorbent were determined, in batch conditions, by changing different experimental parameters such as initial CV dye concentrations (5, 10, 20, 30, and 40 mg L–1), contact time (15, 30, 60, 120, and 180 min.), adsorbent doses (0.025, 0.05, 0.1, 0.2, and 0.3 g), temperature (25, 35, 45, and 55°C), and pH (3, 5, 7, 9, and 11). The adsorption mechanisms of CV dye onto the P. capillacea biomass were examined using various analytical techniques such as FTIR, BET, UV–Visible, and SEM. These characterizations suggest the average BET surface area of P. capillacea was 87.17 m2 g–1 and a pore volume of 0.10368 cc g−1. Moreover, according to the FTIR study, the dye has been deposited inside the adsorbent’s pores after adsorption. The adsorption behavior of the adsorbent was investigated by performing both kinetic and equilibrium isothermal studies in batch conditions at 25°C. Also, the thermodynamic factors showed the exothermic nature and physisorption of the adsorption process, which tends to be spontaneous at lower temperatures. In addition, Langmuir, Dubinin-Radushkevich, Freundlich, and Tempkin isotherm models were selected to evaluate the adsorption of CV dye on P. capillacea. The equilibrium adsorption data were best represented by the Freundlich, indicating multilayer adsorption on the heterogeneous surface. The qe experiment and calculation values for the Pseudo-Second-Order and interparticle diffusion kinetic models were determined. The results showed that, under optimum conditions P. capillacea exhibited 98% removal of CV dye from synthetic wastewater. Moreover, it will help to regenerate the adsorbents that can be reused to adsorb CV dye ions and develop a successful adsorption process. Finally, this study concluded that the dried powdered form of P. capillacea is an attractive source for adsorbing CV dye from aqueous solution.